Effective Eddy Current Braking at Low and High Vehicular Speeds – A Simulation Study - , Alumona Louis Olisaeloka; , Azaka Onyemazuwa Andrew; , Nwadike Emmauel Chinagorom (Archives of Current Research International, 2017)
Conventional eddy current braking is limited in effectiveness to only the high vehicular speed region. As the vehicle slows, the conventional eddy current brake loses effectiveness. This inherent drawback is due to the use of static/stationary magnetic field in the brake system. This study presents a solution - the use of rotating magnetic field in the brake system. By the study design, the conducting brake disc rotates between the poles of an electromagnet. A constant air-gap separates the disc from the poles on either side. The electromagnet windings (each with a core) are made poly-phase so that when an equivalent poly-phase source supplies ac to the electromagnet windings, a rotating magnetic field is obtained. The rotating magnetic field comes on when the brake is applied and eddy current is induced in the conducting brake disc to effectuate retardation. The brake disc is coupled to the road wheel so that retardation of the brake disc transmits directly to the road wheel. The eddy current braking torque is a measure of the braking power. The braking torque varies directly as the relative speed between the conducting brake disc and the eddy current brake magnetic field. The braking torque is studied under three main conditions. These are when the brake disc and the magnetic field rotate in opposite directions, when the brake disc and the magnetic field rotate in the same direction and when the wheel is stationary with only the magnetic field rotating. Braking performance is studied in terms of stopping a vehicle, slowing and preventing motion. Results show that stopping and slowing are achieved when the magnetic field rotates opposite the direction of the brake disc rotation. For stationary wheel, motion will not occur as long as the torque which tends to be tractive is counterbalanced by friction at the wheels and the vehicular mass inertia. Modeling and simulation in this study are done using Mat Lab – Simulink software.